Adult ADHD: Prevalence and Clinical Correlates in a Sample of Italian Psychiatric Outpatients. Issue 4 (February 2021) - Valsecchi, Paolo; Nibbio, Gabriele; Rosa, Jennifer; Tamussi, Elena; Turrina, Cesare; Sacchetti, Emilio; Vita, Antonio
Objective: ADHD remains a largely underdiagnosed disorder in Europe and especially in Italy. Aims of the present study were to assess the prevalence of ADHD and its clinical and demographic correlates in a large sample of Italian outpatients.Method: 634 outpatients accessing psychiatric services were assessed with the Mini-International Neuropsychiatric Interview (MINI) Plus V. 5.0.0 interview and the Adult ADHD self-report Scale Symptoms Checklist (ASRS)-V 1.1 Short Form. Patients positive to the ASRS-V 1.1 were assessed with the Diagnostic Interview for ADHD in Adults (DIVA) 2.0.Results: Of the total patients' sample, 81 (12.8%) were positive on the ASRS-V 1.1. After performing the DIVA 2.0, 44 patients (6.9%) met the criteria for Adult ADHD. Significant clinical and demographic differences between ADHD positive and negative groups were found.Conclusion: The prevalence and correlates of ADHD comorbidity in our outpatient psychiatric population were comparable to those found in other high-income countries. Considering the prevalence of ADHD and its impact on functioning, implementing specific knowledge on this subject is needed.